Retrospective Evaluation of Challenging Delayed Union and Non-union Encountered in Dogs: 16 Cases (2012-2018) - İnal, KS and Önyay, T and Yılmaz, MS and Yardımcı, C and Özak, A (Journal of the Hellenic Veterinary Medical Society, 2023)
This paper aims to showcase some challenging delayed union and non-union cases, explain their possible causes and the treatment processes they underwent. Most non-union cases included in this study required at least two surgical interventions, and the main reasons for the consecutive interventions were either compromised vasculature of the soft tissues due to extreme trauma or infection. The final successful procedure for cases with excessive soft tissue trauma was external fixator application in most cases. Bone plates were more successful in cases with infection or had poor owner compliance. Minimally invasive external fixator implementation seems to be efficient in preserving the compromised vasculature of the bone while bone plates show better results in cases with localized infection. Harvesting bone grafts from the iliac crest was very practicable, required little time and should be utilized in every possible non-union case given their obvious benefits.